GE_GERICHTE P/5662/2022 vom 26. Mai 2025 - GE Cour de justice (2025)
INCESTE;VIOL;INFRACTIONS CONTRE L'INTÉGRITÉ SEXUELLE;ACTE D'ORDRE SEXUEL AVEC UN ENFANT;CONTRAINTE SEXUELLE | CP.180.al1; CP.181; CP.183.al1.ch1; CP.187.ch1; CP.189.ch1; CP.190.ch1; CP.190.ch3; CP.213.al1; CP.189.al2